STUDY ON CREEP PROPERTY OF HIGH PRESSURE PIPE OF THERMAL POWER PLANT IN SERVICE FROM SMALL PUNCH TEST - GENG JinFeng; MA DongFang; XU Liang; WANG YanQing; WU KeHua (Jixie qiangdu)
The creep test of high pressure steam pipe of a thermal power plant was carried out at 566 degree by using SPT technology. The deflection curve with time under different stress levels was obtained. In order to obtain the steady-state creep characteristics of the material,the Chakrabarty model and inverse finite element method on small punch creep test results were analyzed,obtained the material parameters of A and n in Norton equation. At the same time,the material parameters of uniaxial creep test and small punch test analysis of the comparative analysis results show that the small punch creep test results and uniaxial creep test results are consistent with each other,but different methods of analysis results of different accuracy.